Drivers and hinders for a fossil-free energy system in the agriculture : a Swedish farmer perspective - Casimir, Justin (SLU/Dept. of Energy and Technology, 2017)
This master thesis looked at the factors supporting and hindering Swedish farmers to produce renewable energy at farms. The main source of data used in this project was a survey answered by 1497 Swedish farmers who were member of the Federation of Swedish Farmers during the winter 2015-2016. To structure the results, Rogers’ theory of diffusion of innovation was used. A literature review completed the survey and assessed its effectiveness. The results showed that economic factors were the most important ones and that personal and business factors were the following most important factors. The results from the survey showed that political factors are only seen as hindering. This project highlighted that the perception of these factors differed depending on if the farms were producing energy for their own use or for selling purpose. For instance, farmers selling energy perceived that political factors, such as the lack of longterm regulations and the complexity of rules, were more hindering their development than what farmers using the energy at the farm perceived. The drivers and hinders were broken down for three renewable energy sources (bioenergy, solar electricity, and wind power) and showed how each technology related to the different factors. Focussing on the economic factors, farmers generating renewable energy from photovoltaics panels or biomass are more satisfied about their investment than farmers who invested in wind power. In order to overcome global warming, society should abandon fossil based practices and adopt fossil free ones. Agriculture has a role play by both reducing its own emission of greenhouse gases being a key actor for the supply of resources for fossil-free based products and services. A way to accelerate the conversion process is to apply measures that develop the existing drivers and reduce the perceived hinders. A sample of measures suggested in this project includes promotion of solutions for the supply of energy for the farm own use based on the current situation, the simplification of the regulations framing the sale of solar and wind power, and the spread of knowledge about both energy and its rules.